Arctic Charr ( Salvelinus alpinus ) in Windermere (Cumbria) - Ellysar Baroudy (Freshwater Biological Assoication, 2010)
This article commences with a brief introduction to Arctic charr (Salvelinusalpinus (L.)) and its distribution in the British Isles. The history ofinvestigations on charr in Windermere is then presented and, finally, recenttrophic changes in the lake and their consequent effects on the salmonidpopulation, are discussed.